Sustained growth in Haiti : pipe-dream or realistic possibility - Lundahl, Mats (1999)
Looks at the fundamental mechanism behind the declining standard of living in rural areas and explores the main present safety value: migration - out of the countryside and into urban areas. Considers some agrarian reform efforts and non traditional crops. Discusses the reasons behind the failure of import substitution in manufacturing; industrial recovery; the competitiveness in the short- and medium-run of the most important branches, as well as some ingredients in a possible industrial strategy. Examines the main present shortcomings and needs of the handicraft sedtor. Looks at the problems in the informal economy and considers the important role in most sectors of education and infrastructure. Evaluates the possibility of increased growth in Haiti in the short- and medium- term.